2022
DOI: 10.5114/aoms/155211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on pro and advanced cycling athletes: A cross-sectional study in Poland

Abstract: IntroductionThe COVID-19 pandemic has affected different communities, yet the data on its impact on cyclists, is scarce.Material and methodsThe present study assessed the training patterns of pro and advanced amateur cycling athletes in Poland (n=130) during the COVID-19 pandemic compared with the pre-pandemic season and in relation to their epidemiological situation and quality of life factors.ResultsThe volume and weekly frequency of training was not decreased during the pandemic. However, their High-Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In Poland, studies showed that athletes adapted the training routines at home. Players in some sports, such as cycling, maintained their volume and frequency of training during the pandemic; however, they reduced the intensity of training by lowering the time spent on high-intensity intervals (Rzymski et al, 2022). In our results, Polish players were training a few times a week, which is similar to the results in pre-pandemic times (Lenartowicz & Ciok, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…In Poland, studies showed that athletes adapted the training routines at home. Players in some sports, such as cycling, maintained their volume and frequency of training during the pandemic; however, they reduced the intensity of training by lowering the time spent on high-intensity intervals (Rzymski et al, 2022). In our results, Polish players were training a few times a week, which is similar to the results in pre-pandemic times (Lenartowicz & Ciok, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…This is important because it is rooted in a social network and the resulting ability to receive informal support that significantly impacts a person’s well-being [ 23 ]. Physical activity was also strongly associated with a reduced risk of severe COVID-19 complications among infected adults [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%